Microwave Assisted Enzymatic Kinetic Resolution of (±)-1-Phenyl-2-propyn-1-ol in Nonaqueous Media. (23rd February 2014) - Devendran, Saravanan; Yadav, Ganapati D.
Abstract : Kinetic resolution of 1-phenyl-2-propyn-1-ol, an important chiral synthon, was studied through trans-esterification with acyl acetate to investigate synergism between microwave irradiation and enzyme catalysis. Lipases from different microbial origins were employed for the kinetic resolution of (R/S)-1-phenyl-2-propyn-1-ol, among which Candida antarctica lipase B, immobilized on acrylic resin (Novozym 435), was found to be the best catalyst in n -hexane as solvent. Vinyl acetate was the most effective among different acyl esters studied. The effect of various parameters was studied in a systematic manner. Definite synergism between microwave and enzyme was observed. The initial rate was improved around 1.28 times under microwave irradiation than conventional heating. Under optimum conditions, maximum conversion (48.78%) and high enantiomeric excess (93.25%) were obtained in 2 h. From modeling studies, it is concluded that the reaction follows the Ping-Pong bi-bi mechanism with dead end alcohol inhibition. Kinetic parameters were obtained by using nonlinear regression. This process is green, clean, and easily scalable as compared to the chemical process.